Professional Counselors' Experiences on Interprofessional Teams in Hospital Settings. (21st September 2021) - Johnson, Kaprea F.; Blake, Jennifer; Ramsey, Hannah E.
Abstract : This qualitative study explored the experiences of 11 professional counselors who work on interprofessional teams in hospital settings. We conducted semistructured interviews and identified four themes using interpretative phenomenological analysis: (a) support patient care and positive team interactions, (b) interprofessional supervision, (c) scope of practice, and (d) ethical considerations. Implications for interprofessional supervision and professional counselors' contribution to interprofessional engagement in hospital settings are discussed.